Fuzzy-defined entities: A key concept to strengthen forensic science foundations? - Brocard, Lionel; Jaquet-Chiffelle, David-Olivier (Forensic science international, 2024)
According to the Sydney Declaration, “Forensic science is [… an] endeavour to study traces […] through their detection, recognition, recovery, examination and interpretation to understand anomalous events of public interest (e.g., crimes, security incidents).” This science is focused on establishing the nature and relationships among entities related to events having a potential legal impact. Entities can be (groups of) persons, objects, activities and their corresponding sources, events and traces. Although uniqueness of an entity has been traditionally accepted as a principle of forensic science, this paper argues and illustrates that such uniqueness is illusory: Not only can an entity evolve spatially and temporally, but at any specific instant, it differs from itself according to the level of precision at which it is considered. Its characteristics vary based on when, how and by whom it is perceived. We introduce the concept of fuzzy entities - defined to formally include some essential uncertainty or imprecision. The essential impreciseness and subjectivity of an entity gives a new perspective that allows us to revisit Kirk's principle of individuality and to propose to replace it with a new principle of fuzzy unicity. We believe that this new perspective has the potential to strengthen forensic science foundations and bring closer its disciplines, which is an important step towards a harmonized forensic science. •There is a broad consensus that forensic science is not sufficiently formalized.•Differences between forensic disciplines may result from model limitations.•Models are based on the core concept of entity which is imprecise.•Acknowledging entity fuzziness helps reformulate fundamental concepts.•Fuzzy-defined fundamental concepts lead to stronger forensic science foundations.